2023
DOI: 10.3390/antiox12030548
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Inflammation in Acute and Chronic Lung Injuries

Abstract: Acute and chronic lung injuries are among the leading causes of mortality worldwide. Lung injury can affect several components of the respiratory system, including the airways, parenchyma, and pulmonary vasculature. Although acute and chronic lung injuries represent an enormous economic and clinical burden, currently available therapies primarily focus on alleviating disease symptoms rather than reversing and/or preventing lung pathology. Moreover, some supportive interventions, such as oxygen and mechanical v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(22 citation statements)
references
References 437 publications
0
22
0
Order By: Relevance
“…Studies have demonstrated that H 2 S can alleviate oxidative stress in hyperoxic conditions by upregulating antioxidant enzymes and reducing reactive oxygen species (ROS) production. In addition, H 2 S can modulate the expression and activity of hypoxia-inducible factor 1α (HIF-1α), a key regulator of oxygen homeostasis, in response to hyperoxia [65].…”
Section: Oxygen Homeostasis In Atherosclerosis and The Role Of Hydrog...mentioning
confidence: 99%
“…Studies have demonstrated that H 2 S can alleviate oxidative stress in hyperoxic conditions by upregulating antioxidant enzymes and reducing reactive oxygen species (ROS) production. In addition, H 2 S can modulate the expression and activity of hypoxia-inducible factor 1α (HIF-1α), a key regulator of oxygen homeostasis, in response to hyperoxia [65].…”
Section: Oxygen Homeostasis In Atherosclerosis and The Role Of Hydrog...mentioning
confidence: 99%
“…CS induces airway inflammation and oxidative stress in the lungs. Even after the cessation of CS exposure, inflammation may persist, fostering a microenvironment conducive to chronic tissue damage through elevated pro-inflammatory cytokines, such as interleukin-6 (IL-6), interleukin-1β (IL-1β), and tumor necrosis factor-α (TNF-α), 2 leading to the infiltration of macrophages, lymphocytes, neutrophils, and other inflammatory cells into small airways. Simultaneously, oxidative stress disrupts redox balance, impairing antioxidant enzymes like superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px), thereby exacerbating the inflammatory process and perpetuating a detrimental loop in COPD pathophysiology.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in the lungs, oxidative stress is a critical factor in the pathogenesis of diseases such as chronic obstructive pulmonary disease (COPD), pulmonary fibrosis, and acute respiratory distress syndrome (ARDS). Oxidative damage in lung tissue can lead to disruption of cellular barrier function, enhanced inflammatory response, and aggravated fibrosis process ( Hecker, 2018 ; Bezerra et al, 2023 ). This pathological condition arises when there is an imbalance between the production of ROS and the lung’s ability to detoxify these harmful compounds or to repair the resulting damage ( Snezhkina et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, brain injury can activate the neuroimmune lung axis, potentially leading to pulmonary pathology ( Ziaka and Exadaktylos, 2021 ). Conversely, lung diseases can impact neural function through oxidative stress and inflammatory pathways ( Bezerra et al, 2023 ). These interactions emphasize the importance of considering the health of two organs in the context of a disease that may initially affect one organ, implying that when one organ experiences stress or damage, it can trigger a cascade of reactions in another organ.…”
Section: Introductionmentioning
confidence: 99%